Reimagining Professional Development for Digital Literacies: Old, New and Pandemic - Wong, Suzanna; Laidlaw, Linda; Liu, Yina (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2021)
During the COVID-19 pandemic teachers have been expected to learn new digital literacy skills, often applying them immediately. While professional development structures within school districts and professional associations are organized to offer supports, teachers may be challenged to gain digital skills within existing professional development models. Within our study, teachers explored technologies with the aim of rethinking frames for teaching and learning literacy. Following the start of the COVID-19 pandemic they shared their experiences, insights and challenges. In our article, we address implications for digital literacy teaching and learning and the need for new ways of approaching teacher development.